The effectiveness of using GeoGebra software on the achievement of tenth grade students in the mathematics curriculum in Ain Al-Basha district schools - Alhanoti, Hisham Yosef (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the effectiveness of using GeoGebra software on the academic achievement of tenth grade students in the mathematics curriculum in the schools of Ain Al-Basha District. An item of multiple choice and (5) essay questions. The study sample consisted of (110) male and female students, who were chosen by the intentional method. The results of the study showed that there were statistically significant differences, at the significance level (α = 0.05) between the mean scores of the students of the first experimental group, which were taught using the (Geogebra) program, and the scores of the students of the fourth group (the control group), which were studied using the usual method attributed to the teaching method. Using (Geogebra, and Ordinary) in favor of the first experimental group, which was studied using the (Jeogebra) program. The researcher recommends the necessity of holding training courses for mathematics teachers, in the use of educational software, in teaching mathematics.
Keywords: GeoGebra software; achievement; tenth grade